A new, fast and convenient method for layering blood or bone marrow over density gradient medium. Issue 7 (July 1995) - Islam, A
Abstract : A density gradient dispenser has been developed, providing a fast, easy and convenient method for layering peripheral blood or bone marrow over a density gradient solution for the isolation of lymphocytes and mononuclear cells. The present approach is just the opposite of the conventional method of layering blood over a density gradient solution. In the conventional method a required amount of density gradient solution is first placed in a centrifuge tube and then blood or marrow is layered on top using a pasteur pipette. In the present method a required amount of blood or marrow is first placed in a centrifuge tube. The required amount of density gradient solution is then gently delivered underneath the blood sample using the newly devised density gradient dispenser. Because of the difference in densities, the released density gradient solution lifts the sample of blood upwards and produces exactly the same blood and density gradient suspension as that produced by the conventional method but is less cumbersome, faster and more convenient.